CONVECTIVE HEAT TRANSFER, FRICTION FACTOR AND THERMAL PERFORMANCE IN A ROUND TUBE EQUIPPED WITH THE MODIFIED V-SHAPED BAFFLE - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2018)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Baffle; Thermal fluids; Friction Factor; Spacecraft and Cryogenic Technologies